New pneumothorax complicating successful treatment of persistent air leak by endobronchial valves. Issue 4 (7th March 2021) - Yeung, Yiu Cheong; Chan, Yu Hong; Ho, Man Ying; Chan, Ming Chiu; Kwok, Hau Chung; Yu, Wai Cho
Abstract: Endobronchial one‐way valves (EBV) have been proposed as a treatment option for persistent air leak (PAL) complicating spontaneous pneumothorax when surgical intervention is considered not feasible. Published case series showed this form of treatment to be generally safe. We report two such cases in which both achieved immediate cessation of air leak and post‐procedural chest radiograph showed significant collapse of the treated lobe, but developed sudden onset of shortness of breath within 24 h after EBV insertion. Chest radiograph showed continued collapse of the treated lobes with enlarged ipsilateral pneumothorax in one patient and new contralateral pneumothorax in the other. Pulmonologists and thoracic surgeons inserting EBV for treatment of PAL should be aware of this possible and important complication. Abstract : The present case report included two cases of pneumothorax after endobronchial valve treatment of persistent air leak (PAL) complicating pneumothorax. The occurrence of this adverse event (the first case showed new ipsilateral pneumothorax and the second case showed new contralateral pneumothorax) shed light to the underlying mechanism of this complication and has not been reported before in the treatment of PAL.